Malaysia Public Expenditures : Managing the Crisis; Challenging the Future - World Bank (Washington, DC, 2013)
Malaysia achieved unprecedented economic growth and dramatic poverty reduction in the two decades prior to 1997. As a result, pressure on public expenditures was alleviated and when the regional financial crisis hit in 1997, the budget was in surplus and public debt had fallen to around 30 percent in GDP. But the crisis brought to the fore issues in public expenditure management that might have remained of less significance in a fast-growing economy: large and increasing off-budget liabilities that could undermine fiscal prudence, accountability, and efficiency in the use of public resources. The government is rethinking its role in tertiary education, tertiary health care, social protection against income risk, and infrastructure. In these areas, there is a potential role for the private sector in provision and financing, and the government's role is gradually shifting from being a provider of these services to a financial supporter and a regulator. In this evolving public-private partnership, the goal of the government is to reduce the fiscal burden while ensuring equity in delivering public services and efficiency in allocating and using public resources. This public expenditure analysis aims to analyze fiscal issues arising from the crisis, gauge the government's public expenditure management system, and assess performance and future challenges in education, health, poverty reduction, and infrastructure.